A taxonomy of high school students' levels of understanding in solving algebraic problems. (28th March 2022) - Egodawatte, Gunawardena
Abstract: The research reported in this article sought to develop a taxonomy of grade 11 students' levels of understanding in algebraic problem-solving tasks. The student sample was from high schools in the province of Ontario in Canada. Problems from four areas in algebra namely, variables, expressions, equations and word problems were chosen to be represented in the test paper. A six-level taxonomy was constructed by analyzing the structure of students' written responses and their subsequent interview transcripts. The first three levels of the taxonomy belong to the application of lower level thinking skills while the last two levels belong to the application of higher level thinking skills. The taxonomy serves two purposes. Teachers can use it for formulating objectives in classroom teaching, and they can also use it as an evaluation tool in constructing assessment items.